CDK9 inhibition blocks the initiation of PINK1-PRKN-mediated mitophagy by regulating the SIRT1-FOXO3-BNIP3 axis and enhances the therapeutic effects involving mitochondrial dysfunction in hepatocellular carcinoma. Issue 8 (3rd August 2022) - Yao, Jingyue; Wang, Jubo; Xu, Ye; Guo, Qinglong; Sun, Yuening; Liu, Jian; Li, Sichan; Guo, Yongjian; Wei, Libin
ABSTRACT: Mitophagy is a type of selective macroautophagy/autophagy that degrades dysfunctional or excessive mitochondria. Regulation of this process is critical for maintaining cellular homeostasis and has been closely implicated in acquired drug resistance. However, the regulatory mechanisms and influences of mitophagy in cancer are still unclear. Here, we reported that inhibition of CDK9 blocked PINK1-PRKN-mediated mitophagy in HCC (hepatocellular carcinoma) by interrupting mitophagy initiation. We demonstrated that CDK9 inhibitors promoted dephosphorylation of SIRT1 and promoted FOXO3 protein degradation, which was regulated by its acetylation, leading to the transcriptional repression of FOXO3-driven BNIP3 and impairing the BNIP3-mediated stability of the PINK1 protein. Lysosomal degradation inhibitors could not rescue mitophagy flux blocked by CDK9 inhibitors. Thus, CDK9 inhibitors inactivated the SIRT1-FOXO3-BNIP3 axis and PINK1-PRKN pathway to subsequently block mitophagy initiation. Moreover, CDK9 inhibitors facilitated mitochondrial dysfunction. The dual effects of CDK9 inhibitors resulted in the destruction of mitochondrial homeostasis and cell death in HCC. Importantly, a novel CDK9 inhibitor, oroxylin A (OA), from Scutellaria baicalensis was investigated, and it showed strong therapeutic potential against HCC and a striking capacity to overcome drug resistance by downregulating PINK1-PRKN-mediated mitophagy. Additionally, because of the moderate and controlled inhibition of CDK9, OA not led to extreme repression of general transcription and appeared to overcome the inconsistent anti-HCC efficacy and high normal tissue toxicity that was associated with existing CDK9 inhibitors. All of the findings reveal that mitophagy disruption is a promising strategy for HCC treatment and OA is a potential candidate for the development of mitophagy inhibitors. Abbreviations: BNIP3: BCL2 interacting protein 3; CCCP: carbonyl cyanide p-trichloromethoxy-phenylhydrazone; CDK9: cyclin dependent kinase 9; CHX: cycloheximide; CQ, chloroquine; DFP: deferiprone; DOX: doxorubicin; EBSS: Earle's balanced salt solution; E64d: aloxistatin; FOXO3: forkhead box O3; HCC: hepatocellular carcinoma; HepG2/ADR: adriamycin-resistant HepG2 cells; MMP: mitochondrial membrane potential; mito-Keima: mitochondria-targeted and pH-sensitive fluorescent protein; MitoSOX: mitochondrial reactive oxygen species; OA: oroxylin A; PB: phosphate buffer; PDX: patient-derived tumor xenograft; PINK1: PTEN induced kinase 1; POLR2A: RNA polymerase II subunit A; p-POLR2A-S2: Ser2 phosphorylation of RNA polymerase II subunit A; PRKN: parkin RBR E3 ubiquitin protein ligase; SIRT1: sirtuin 1.